1998
DOI: 10.1126/science.280.5363.590
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Visualization of DNA Double-Strand Break Repair in Human Fibroblasts

Abstract: A method was developed to examine DNA repair within the intact cell. Ultrasoft x-rays were used to induce DNA double-strand breaks (DSBs) in defined subnuclear volumes of human fibroblasts and DNA repair was visualized at those sites. The DSBs remained in a fixed position during the initial stages of DNA repair, and the DSB repair protein hMre11 migrated to the sites of damage within 30 minutes. In contrast, hRad51, a human RecA homolog, did not localize at sites of DNA damage, a finding consistent with the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
276
3
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(297 citation statements)
references
References 42 publications
(8 reference statements)
15
276
3
3
Order By: Relevance
“…In previous studies, it was observed that XP-V cells with impaired p53 employed an MRNdependent recombination pathway in response to UV damage [17,25,27,28], implying DSBs are generated during replication arrest [49,[52][53][54]. We observed that p53 suppression leads to a similar increase in the frequency of normal and XP-V cells with Mre11 foci, even without UV irradiation.…”
Section: Discussionsupporting
confidence: 63%
“…In previous studies, it was observed that XP-V cells with impaired p53 employed an MRNdependent recombination pathway in response to UV damage [17,25,27,28], implying DSBs are generated during replication arrest [49,[52][53][54]. We observed that p53 suppression leads to a similar increase in the frequency of normal and XP-V cells with Mre11 foci, even without UV irradiation.…”
Section: Discussionsupporting
confidence: 63%
“…These processes may be conserved, as broken DSB ends can exhibit limited or pronounced mobility in mammals [63][64][65][66] . Thus, it will be important to determine whether motor complexes contribute to DSB repair in different organisms including human.…”
Section: Discussionmentioning
confidence: 99%
“…The gene product defective in NBS, p95 or nibrin, is a component of the large multiprotein complex containing hRad50 and hMre11, nuclear proteins implicated in the NHEJ recombinational DNA repair pathway (Varon et al, 1998;Carney et al, 1998;Dolganov et al, 1996;Featherstone and Jackson, 1998). In response to IR, hMre11 and hRad50 form nuclear foci in close proximity to DSBs and the formation of these foci is markedly reduced in both NBS and AT cells (Maser et al, 1997;Dolganov et al, 1996;Carney et al, 1998;Nelms et al, 1998). Interestingly, AT cells form unusually high numbers of foci containing the homologous recombinational repair protein, hRad51 (Maser et al, 1997).…”
Section: At Phenotypementioning
confidence: 99%